Synthetic Lipopeptide Enhances Protective Immunity Against Helicobacter pylori Infection - Xue, Ruo-Yi; Guo, Mu-fei; Guo, Ling; Liu, Chang; Li, Sun; Luo, Jiao; Nie, Li; Ji, Lu; Ma, Cong-Jia; Chen, Da-Qun; Sun, Si; Jin, Zhe; et al. (Frontiers in Immunology, 2019)
Over fifty percent of the people around the world is infected with Helicobacter pylori (H. pylori), which is the main cause of gastric diseases such as chronic gastritis and stomach cancer. H. pylori adhesin A (HpaA), which is a surface-located lipoprotein, is essential for bacterial colonization in the gastric mucosa. HpaA had been proposed to be a promising vaccine candidate against H. pylori infection. However, the effect of non-lipidated recombinant HpaA (rHpaA) to stimulate immune response was not very ideal, and the protective effect against H. pylori infection was also limited. Here, we hypothesized that low immunogenicity of rHpaA may attribute to lacking the immunostimulatory properties endowed by the lipid moiety. In this study, two novel lipopeptides, LP1 and LP2, which mimic the terminal structure of the native HpaA (nHpaA), were synthesized and TLR2 activation activity was confirmed in vitro. To investigate whether two novel lipopeptides could improve the protective effect of rHpaA against the infection of H. pylori, groups of mice were immunized either intramuscularly or intranasally with rHpaA together with LP1 or LP2. Compared with rHpaA alone, the bacterial colonization of the mice immunized with rHpaA plus LP2 via intranasal route was significantly decreased and the expression levels of serum IgG2a, IFN-γ, and IL-17 cytokines in spleen lymphocyte culture supernatant increased obviously, indicating that the enhanced protection of LP2 may be associated with elevated specific Th1 and Th17 responses. In conclusion, LP2 has been shown to improve the protective effect of rHpaA against H. pylori infection, which may be closely related to its ability in activating TLR2 by mimicking the terminal structure of nHpaA.